Pengaruh Intensitas Interaksi Sosial Media Bermuatan Kristiani Terhadap Pembentukan Karakter Peserta Didik Di SMPN 1 Cikampek - Wesly, Juni; Sugiat, Sugiat (Sekolah Tinggi Teologi Kadesi Bogor, 2025)
Social media and teenagers are inseparable. It is undeniable that the sophistication of features found on various devices has made all thoughts and activities at least in contact with devices. The spiritual life of Christian congregations, including teenagers, is often influenced by various external factors, including social media, therefore research is needed to determine the intensity of Christian social media interactions on the character development of students. This research is a quantitative descriptive research with primary data sources obtained from the results of questionnaires from the sample, namely all Christian students at SMPN 01 Cikampek, data obtained from questionnaire entries were analyzed by testing validity, reliability, and correlation between research variables. The results showed that a total of 22 (61%) samples often accessed Christian content. The correlation results show a result of 0.369 with a significance value of 0.027, this shows a weak and significant relationship that students who often access Christian content have good character development. If social media is used wisely and directed sufficiently to Christian content then character development will be good.